Focus on podocytes: diabetic kidney disease and renal fibrosis — a global bibliometric analysis (2000–2024) - An, Dong-Yang; Tan, Jun; Lu, Yan-Dan; Wen, Ze-Huai; Bao, Yi-Ni; Yao, Zhou-Hui; Chen, Zi-Yan; Wang, Ping-Ping; Zhou, Wei; Yang, Qiao; Hao, Min (Frontiers in Pharmacology, 2024)
Background Diabetic kidney disease (DKD) is a common pathway to End-stage renal disease (ESRD). Podocytes are crucial due to their dual barrier functions in kidney diseases. Their role in renal fibrosis and DKD regulatory mechanisms is increasingly studied. However, bibliometric research in this field has not been explored. Methods 1,250 publications from Jan. 1, 2000, to Feb. 16, 2024, were retrieved from the WoSCC database and analyzed by the Web of Science results analysis tool, VOSviewer, and CiteSpace. Results Our scrutiny reveals that authors Liu Youhua, Fogo Agnes B, and Zhao Yingyong have made substantial contributions to this domain. Notably, “Kidney International” has the highest volume of publications in this area. Furthermore, our analysis identifies ten co-citation clusters: DKD, IncRNA, reactive oxygen species, glomerulosclerosis, Poria cocos, glomerular diseases, fibroblasts, connective tissue growth factor, coagulation, and Wnt. Recent research accentuates keywords such as autophagy, TRPC6, ERS, epigenetics, and NLRP3 inflammasome as frequently occurring terms in this field. The prevailing research hotspot keywords include autophagy, biomarker, and exosomes. Conclusion Through the utilization of bibliometric tools and knowledge graph analysis, we have undertaken a comprehensive review of the intricate nexus between podocytes in DKD and renal fibrosis. This study imparts valuable insights to scholars regarding the dynamic evolution of this association and delineates prospective research avenues in this pivotal realm.